Dopamine-induced arrestin recruitment and desensitization of the dopamine D4 receptor is regulated by G protein-coupled receptor kinase-2 - Burström, Viktor; Ågren, Richard; Betari, Nibal; Valle-León, Marta; Garro-Martínez, Emilio; Ciruela, Francisco; Sahlholm, Kristoffer (Frontiers in Pharmacology, 2023)
The dopamine D4 receptor (D4R) is expressed in the retina, prefrontal cortex, and autonomic nervous system and has been implicated in attention deficit hyperactivity disorder (ADHD), substance use disorders, and erectile dysfunction. D4R has also been investigated as a target for antipsychotics due to its high affinity for clozapine. As opposed to the closely related dopamine D2 receptor (D2R), dopamine-induced arrestin recruitment and desensitization at the D4R have not been studied in detail. Indeed, some earlier investigations could not detect arrestin recruitment and desensitization of this receptor upon its activation by agonist. Here, we used a novel nanoluciferase complementation assay to study dopamine-induced recruitment of β-arrestin2 (βarr2; also known as arrestin3) and G protein-coupled receptor kinase-2 (GRK2) to the D4R in HEK293T cells. We also studied desensitization of D4R-evoked G protein-coupled inward rectifier potassium (GIRK; also known as Kir3) current responses in Xenopus oocytes. Furthermore, the effect of coexpression of GRK2 on βarr2 recruitment and GIRK response desensitization was examined. The results suggest that coexpression of GRK2 enhanced the potency of dopamine to induce βarr2 recruitment to the D4R and accelerated the rate of desensitization of D4R-evoked GIRK responses. The present study reveals new details about the regulation of arrestin recruitment to the D4R and thus increases our understanding of the signaling and desensitization of this receptor.